The use of artificial songs to assess song recognition in imprinted female songbirds: a concept proposal - Makioka, Hiroharu; Lewis, Rebecca N.; Soma, Masayo (Frontiers in Psychology, 2024)
We propose an experimental paradigm to examine acoustic features responsible for song preference and recognition in songbirds. Song preference in female songbirds is often influenced by early song experience. That is why several Estrildid species, including our subject species, the Java sparrow (Padda oryzivora), are known to show an imprinted preference for their father's songs. After confirming that Java sparrow females preferred their father's song compared to non-imprinted through song playbacks (first step), we repeated the playback tests in the same subjects using synthesized stimuli (second step). To create synthesized stimuli, we removed all the complex frequency modulations and subharmonics from song notes that we used for the first step playback tests to see the effect of spectrometric features on song recognition. The results indicated that females showed higher rate of calling towards synthesized father song stimuli, suggesting that the macroscopic patterns would play more important roles in song recognition than the microscopic acoustic features. Although we looked at spectrometric features and father-imprinted song preference in this study, similar testing can be applied in many ways to test preference for local dialects or subspecies-specific songs.